2017
DOI: 10.1093/reseval/rvx004
|View full text |Cite
|
Sign up to set email alerts
|

Is the prominent scientist the one who becomes an inventor? A matching of Swedish academic pairs in nanoscience to examine the effect of publishing on patenting

Abstract: Nanoscience is an innovation intensive interdisciplinary field, where science and technology are closely related during development. Sweden represents an interesting setting to examine how they are related, because a high fraction of the total Swedish academic patents can be classified as Nanoscience. Combining bibliometric data from Web of Science, patent data from EPO and data from Swedish universities, this paper identifies all authors and all inventors listed on patents who work at universities, within nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 78 publications
(47 reference statements)
1
8
0
Order By: Relevance
“…Scholars with a higher number of publications are more likely to apply for academic patents (Fabrizio & Minin, 2008). This positive relationship between publication and academic patenting is also supported by other empirical studies (Bourelos et al, 2017; Grimm & Jaenicke, 2015; Lee, 2019). In addition, a few studies have argued that there is no significant relationship between publication and patents, or there is a curvilinear or negative relationship (Blumenthal & David, 1997; Crespi et al, 2011; Gulbrandsen & Smeby, 2005).…”
Section: Theoretical Background and Hypothesis Developmentsupporting
confidence: 81%
“…Scholars with a higher number of publications are more likely to apply for academic patents (Fabrizio & Minin, 2008). This positive relationship between publication and academic patenting is also supported by other empirical studies (Bourelos et al, 2017; Grimm & Jaenicke, 2015; Lee, 2019). In addition, a few studies have argued that there is no significant relationship between publication and patents, or there is a curvilinear or negative relationship (Blumenthal & David, 1997; Crespi et al, 2011; Gulbrandsen & Smeby, 2005).…”
Section: Theoretical Background and Hypothesis Developmentsupporting
confidence: 81%
“…The literature suggests that nanotechnology is an interdisciplinary field positioned between physics and chemistry, with strong elements from other scientific fields such as life sciences and material science (Leydesdorff 2008;Leydesdorff and Zhou 2007;Hullmann and Meyer 2003;Huang et al 2011). Previous research also suggests that the prominent scientists in nanotechnology also have a higher probability of becoming prominent inventors with many, well cited patents (Bourelos et al 2017). These characteristics mean that nanotechnology may be relevant for many industrial applications and breakthrough inventions, with many underlying scientific fields and technological components.…”
Section: Nanotechnology Patents As Indicative Of Emerging Technologiesmentioning
confidence: 99%
“…Taking patents as indicative of technology, we identify patents which have both delayed recognition and high impact. We do so in the empirical area of nanotechnology, because it has been identified as an emerging technology with extensive science-technology interactions (Meyer 2001;Meyer et al 2010;Bourelos et al 2017) and identified by the European Commission (2012) as a KET, or Key Enabling Technology. We do so based on data extracted from the European Patent Office (EPO) dataset PATSTAT for the years 1956-2018.…”
mentioning
confidence: 99%
“…Research agreements, consultancy, and joint research are usually the relationships considered most important by several authors, along with patent licensing (Giannopoulou et al, 2010). In this respect, there is a concern about the possibility of attention shifting excessively to intellectual property rights at the expense of publishing research results -despite prior evidence indicating that patenting and publishing are complementary activities (Bourelos et al, 2017). Notwithstanding the possibility of contributing in different ways to an innovation environment, uni-versities embedded in peripheral regions face severe limitations regarding the availability of a research infrastructure that meets the needs of business partners.…”
Section: An Integrative Perspective On University-industry Interactio...mentioning
confidence: 99%